2002
DOI: 10.1016/s0042-6989(02)00388-7
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of objects from backgrounds in visual search tasks

Abstract: In most visual search experiments in the laboratory, objects are presented on an isolated, blank background. In most real world search tasks, however, the background is continuous and can be complex. In six experiments, we examine the ability of the visual system to separate search items from a background. The results support a view in which objects are separated from backgrounds in a single, preattentive step. This is followed by a limited-capacity search process that selects objects that might be targets for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
122
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 62 publications
13
122
1
2
Order By: Relevance
“…Many visual tasks (e.g., visual search) take this rapid figure-ground assignment for granted. Only recently has the role of figure-ground assignment in visual search been tested explicitly (by Wolfe, Oliva, Horowitz, Butcher, & Bompas, 2002). In accord with our results reported here, Wolfe et al concluded was that the search items were separated from the background preattentively.…”
Section: Discussionsupporting
confidence: 90%
“…Many visual tasks (e.g., visual search) take this rapid figure-ground assignment for granted. Only recently has the role of figure-ground assignment in visual search been tested explicitly (by Wolfe, Oliva, Horowitz, Butcher, & Bompas, 2002). In accord with our results reported here, Wolfe et al concluded was that the search items were separated from the background preattentively.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Wolfe et al (2002;see also Harris et al, 1979) proposed that search items might be processed in parallel, even if they are selected by attention in series. Wolfe (2003) likened this process to a car wash that is large enough to accommodate several cars at once but that can only accept the cars in series.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that looming objects receive enhanced processing before or after initial selection has taken place (see, e.g., Harris, Shaw, & Bates, 1979;Wolfe, 2003;Wolfe, Oliva, Horowitz, Butcher, & Bompas, 2002). That is, the RT advantage may lie not in the ability of looming objects to capture attention, but in the processing they receive pre-or postselection.…”
Section: Methodsmentioning
confidence: 99%
“…Background complexity is known to reduce target recognition and increase search times for targets in humans and other animals (Wolfe et al 2002;Bond and Kamil 2006;Bravo and Farid 2008). If we assume similar search and image segregation processes in relevant vertebrate predators, then camouflage is likely to be more effective in heterogeneous environments (Merilaita et al 1999;Merilaita 2003), particularly in cuttlefish, where adaptive camouflage can be utilized to match microhabitat attributes (e.g., Hanlon et al 2007Hanlon et al , 2009.…”
Section: Background Differencesmentioning
confidence: 99%